Neutrophils aggravate inflammatory lesions in intestinal organoids from necrotizing enterocolitis - Heuer, Kim M.; Boettcher, Michael; Raluy, Laia Pagerols; Hagens, Johanna; Kolman, Jan P.; Bunders, Madeleine J.; Wesche, Jasmin; Knopf, Jasmin; Herrmann, Martin; Reinshagen, Konrad; Vincent, Deirdre (Frontiers in immunology, 2025)
IntroductionNecrotizing enterocolitis (NEC) is a leading cause of neonatal death and long-term morbidity, involving complex pathophysiology including prematurity, abnormal bacterial colonization, and ischemia-reperfusion injury, partially mediated by neutrophils. However, the limitations of current animal models hinder the development of targeted therapies for NEC. Thus, this study aimed to develop a human intestinal organoid model for NEC to investigate its pathophysiology, understand neutrophil involvement, and bridge animal and human research.MethodsOrganoid cultures were established from human neonatal intestinal samples with NEC (n=7) and without gut inflammation (controls, n=7), treated with lipopolysaccharides (LPS), and/or cocultured with neutrophils. Flow cytometry quantified neutrophil survival (propidium iodide/Annexin-V), activation (CD11b/CD66b), and TLR-4 expression, as well as organoid TLR-4 expression and apoptosis markers. NEC status and neutrophil recruitment were analyzed using immunofluorescence.ResultsAfter LPS administration, NEC organoids showed significantly increased TLR-4 expression, intestinal apoptosis markers, and NEC scores compared to controls, with more pronounced differences after neutrophil addition. Neutrophil activation markers were elevated when cocultured with both NEC and control organoids, but TLR-4 expression increased only with NEC organoids.DiscussionThe findings suggest that epithelial cells from NEC patients have a heightened innate TLR-4 expression upon LPS stimulation, potentially contributing to NEC development. LPS stimulation resulted in more pronounced NEC-like lesions in NEC organoids, which were exacerbated by neutrophils. This model demonstrates that neutrophils might contribute to NEC manifestation and maintenance and that NEC organoids can reflect disease aspects, potentially aiding in the development of targeted therapies.
Gesehen am 30.09.2025